Partial Trisomy 13 and Partial Monosomy 8 Mosaicism Secondary to an Unbalanced De Novo Translocation: Highlighting an Uncommon Chromosomal Abnormality. (November 2013) - Baranello, Giovanni; Cesaretti, Claudia; Zambonin, Fabio; Casalone, Rosario; Granata, Paola; Esposito, Silvia; Alfei, Enrico; Natacci, Federica
Few cases of mosaicism involving a normal cell line and an unbalanced autosomal translocation have been reported so far. No cases of partial trisomy 13 and partial monosomy 8 mosaicism have been published. The authors report a new patient with partial trisomy 13 and partial monosomy 8 mosaicism due to an unbalanced translocation (13/8). A postzygotic mitotic exchange of nonhomologous chromatids followed by the loss of one of the translocated chromatids has been hypothesized as the potential underlying mechanism. Although a clear correlation of the clinical features of the patient with his chromosomal abnormality can be challenging, dysmorphic features, hyperactive behavior, moderate developmental delay, and tonic-clonic seizures can be interpreted as secondary to the particular genotype of the patient. These findings should be taken into account in the diagnostic process of patients presenting with multiple congenital anomalies and/or mental retardation conditions.